Avaliação histológica do capeamento pulpar direto com Hidróxido de Cálcio, MTA e Biodentie® em ratos Wistar - Preczevski, Ana Paula (2016)
The main purpose of Restorative Dentistry is, through an appropriate treatment, to protect and restore the pulp function, thereby maintaining the dental vitality. The pulp capping is defined as a treatment of an exposed vital pulp exposure with a sealing material to facilitate the formation of reparative dentin and maintain their vitality. The aim of this study was to compare the capacity of three capping materials on the induction of reaparadora dentin. 54 Wistar rats were used, between 21-24 days old, were randomly divided into 3 groups, using as capping materials calcium hydroxide, MTA and Biodentine®. Circular cavities on the first molars were performed in order to make the pulp exposure and the corresponding capping material used for each group. After a period of 7, 14 and 21 days, animals were euthanized, the jaws were removed and fixed for subsequent slides stained with hematoxylin and eosin for histological analysis of the pulp inflammatory response and formation of mineralized barrier. Data were subjected to statistical analysis using the Kruskal-Wallis test, followed by Dunn's test with 95% significance level. All materials studied were able to induce the formation of mineralized tissue; however the MTA and Biodentine® materials responded better in mineralized structure formation and decreased pulp inflammatory response.